Using authentic resources for medical students’ motivation in English learning process. - Honchar, Kateryna; Tryhub, Halyna; Khnykina, Оksana (My University, 2024)
The article investigates the resources for students’ motivation of English learning process. The current stage of development of Ukraine's international relations with other countries requires a revision of the foreign language teaching process in higher education. Special emphasis should be paid to the effectiveness of foreign language learning. The expansion of international contacts highlights the need for training a specialist who can communicate with representatives of other countries not only at the household level, but also in professional activities. First of all, this concerns specialists in those professions related to intercultural communication (international internships, participation in international conferences, etc.). The English learning process of many Ukrainian medical colleges and universities is mainly based on non-authentic materials. Few studies have been conducted to explore the implications of authentic materials in learning English for Specific Purposes (ESP), for medicine in particular. The current study explores students’ perception of these resources in learning medical English. In order to make the learning process more effective, an analysis of authentic English language manuals for medical professionals was made. The data were obtained based on a questionnaire filled out by medical students of Lesya Ukrainka Volyn National University. The students were required to assess different aspects of both authentic and nonauthentic materials. The ultimate goal of the analysis is to determine the educational efficiency of the aforementioned textbooks and the students’ motivation for English learning. The findings showed that the participants had positive attitudes toward using authentic resources and that they preferred them to non-authentic ones. Authentic resources provide a beneficial effect on the development of students’ language skills in their professional area.
Keywords: first-year English major students; English writing skills; teaching strategies and techniques; learning strategies; skills development; college; 811.111:378